2008
DOI: 10.1359/jbmr.080403
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of the Vitamin D Receptor in the Zebrafish, Danio rerio

Abstract: Vitamin D and vitamin D metabolites such as 25(OH) 2 D 3 ] circulate in the serum of fish. The receptor for 1␣,25(OH) 2 D 3 (VDR) has previously been cloned from fish intestine, and ligand binding assays have shown the presence of the VDR in the gills, intestine, and liver of fish. Using immunohistochemical methods with specific antibodies against the VDR, we now report that the VDR is widely expressed in tissues of the adult male and female zebrafish, Danio rerio, specifically in epithelial cells of gills,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…42 VDR is widely expressed in nearly all zebrafish tissues-not only related to calcium transport such as gills, kidney and intestine but also in bone and many endocrine tissues, brain and other tissues-starting already early in its embryonic development. 39,43 Such widespread distribution of VDR was also found in other fish such as rainbow trout. 44 1,25(OH) 2 D 3 also regulates the calcium-transporting transient receptor protein (TRP) genes and thereby increases calcium influx and the calcium content of zebrafish embryos 45,46 and rainbow trout.…”
Section: Origin Of the Vitamin D Endocrine System In Vertebratesmentioning
confidence: 58%
“…42 VDR is widely expressed in nearly all zebrafish tissues-not only related to calcium transport such as gills, kidney and intestine but also in bone and many endocrine tissues, brain and other tissues-starting already early in its embryonic development. 39,43 Such widespread distribution of VDR was also found in other fish such as rainbow trout. 44 1,25(OH) 2 D 3 also regulates the calcium-transporting transient receptor protein (TRP) genes and thereby increases calcium influx and the calcium content of zebrafish embryos 45,46 and rainbow trout.…”
Section: Origin Of the Vitamin D Endocrine System In Vertebratesmentioning
confidence: 58%
“…The few studies that have been carried out on fish deal with the metabolic transformation of the vitamin in both liver and kidney [2,14,[30][31][32], the establishment of plasma levels of vitamin D metabolites [12,13,33,34], the identification of vitamin D plasma binding protein [35,36] and the expression, regulation and evolution of vD receptor in different organs [26,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Mehrad and colleagues (2011) reported that inclusion of ascorbic acid at levels of 1000 mg/kg of feed increased growth rates, body weight, and fecundity in zebrafish. Vitamin D and its metabolites circulate in the blood of the zebrafish, and receptors for this vitamin are widely distributed in many tissues (Craig et al 2008), suggesting its potential importance as a dietary nutrient (Miller et al 2010). Lebold and colleagues (2011) fed zebrafish diets that were deficient in vitamin E (alpha-tocopherol); survival of offspring of deficient adults was lower, malformations resulted, and fatty acid profiles were altered, indicating the importance of vitamin E as a nutrient.…”
Section: Diet Developmentmentioning
confidence: 99%